A SMARCA2 Mutation in the First Case Report of Nicolaides-Baraitser Syndrome in Latin America: Genotype-Phenotype Correlation - Ana Isabel Sánchez; Jorge Armando Rojas (Case Reports in Genetics)
Nicolaides-Baraitser syndrome (NCBRS) is a rare and well-recognized entity that was first described in 1993, with a prevalence that is currently not known. It is recognized as a distinctive entity, with some variability in its signs and symptoms. The most important characteristics include intellectual disability, peculiar facial features including sparse scalp hair, coarse facial features, low frontal hairline, and microcephaly, and seizures. Additional features may include epicanthic folds, thin upper lip vermilion with thick lower lip vermilion, skeletal abnormalities, and severe language impairment. The disorder is inherited in an autosomal dominant manner caused by de novo mutations in the SMARCA2 gene, with most being missense mutations. We report a young adult patient with NCBRS and, to our knowledge, the first case report of the syndrome in Latin America with a confirmed molecular diagnosis and a mild-to-moderate phenotype.